1991
DOI: 10.1038/351145a0
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of cardiac pacemaker channels by intracellular cyclic AMP

Abstract: Cyclic AMP acts as a second messenger in the modulation of several ion channels that are typically controlled by a phosphorylation process. In cardiac pacemaker cells, adrenaline and acetylcholine regulate the hyperpolarization-activated current (if), but in opposite ways; this current is involved in the generation and modulation of pacemaker activity. These actions are mediated by cAMP and underlie control of spontaneous rate by neurotransmitters. Whether the cAMP modulation of if is mediated by channel phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
513
5
6

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(557 citation statements)
references
References 28 publications
33
513
5
6
Order By: Relevance
“…Several reports indicate that activated G8 protein may mediate a phosphorylation-independent influence on certain membrane ion conductances (Yatani, Codina, Imoto, Reeves, Birnbaumer & Brown, 1987;Schubert, VanDongen, Kirsch & Brown, 1989;Yatani, Okabe, Codina, Birnbaumer & Brown, 1990). Intracellular cAMP has been suggested as directly activating cardiac pacemaker channels (DiFrancesco & Tortora, 1991). It is therefore necessary to know whether G8 or cAMP have directly affected f,-adrenergic stimulation of Ip.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that activated G8 protein may mediate a phosphorylation-independent influence on certain membrane ion conductances (Yatani, Codina, Imoto, Reeves, Birnbaumer & Brown, 1987;Schubert, VanDongen, Kirsch & Brown, 1989;Yatani, Okabe, Codina, Birnbaumer & Brown, 1990). Intracellular cAMP has been suggested as directly activating cardiac pacemaker channels (DiFrancesco & Tortora, 1991). It is therefore necessary to know whether G8 or cAMP have directly affected f,-adrenergic stimulation of Ip.…”
Section: Discussionmentioning
confidence: 99%
“…HR as well as I f current are directly modulated by sympathetic and parasympathetic activities (DiFrancesco et al, 1989;DiFrancesco & Tortora, 1991;Guth & Dietze, 1995). It has been shown that I f current of sinoatrial node pacemaker cells is affected by adrenergic stimulation (DiFrancesco & Tortora, 1991) and that ivabradine is a usedependent I f current blocker (Bois et al, 1996;Bucchi et al, 2002).…”
Section: X-j Du Et Almentioning
confidence: 99%
“…It has been shown that I f current of sinoatrial node pacemaker cells is affected by adrenergic stimulation (DiFrancesco & Tortora, 1991) and that ivabradine is a usedependent I f current blocker (Bois et al, 1996;Bucchi et al, 2002). Therefore, it is expected that the efficacy of ivabradine on HR would be modulated by alterations in the sympathetic activity.…”
Section: X-j Du Et Almentioning
confidence: 99%
“…Cyclic nucleotides interact directly with HCN channels through a C-terminal cyclic nucleotide binding domain (CNBD). cAMP increases conductance and shifts I h voltage dependence to more depolarized potentials (DiFrancesco and Tortora 1991). I h may influence integration of postsynaptic events by calibrating membrane resting potential and controlling membrane resistance.…”
Section: Introductionmentioning
confidence: 99%